PREVALENCE OF PREGNANCY-RELATED ANXIETY - Risqi Utami; Melinda Melinda (Yayasan Media Utama Sains, 2024)
Introduction: Maternal anxiety refers to the experience of elevated anxiety symptoms during pregnancy and the transition to parenthood, which is accompanied by significant physiologic and psychological changes. Objective: To identify the factors contributing to pregnancy-related anxiety and evaluate its frequency among first-time pregnant women in the third trimester. The literature was searched using Scopus, Science Direct, PubMed, and Web of Science as research databases. Following PRISMA guidelines, the search criteria encompassed the preceding five years, explicitly emphasizing the period from 2019 to 2023. Results: After applying the criteria for inclusion and exclusion, the assessment identified a total of 12 articles that are suitable for use in the systematic review. Conclusion: The findings substantiate the need for increased support for pregnant women to mitigate anxiety symptoms and facilitate their adjustment to the changes associated with pregnancy.